Methodological proposals for the study of consumer experience - Larissa Becker (Emerald, 2022)
Purpose: As the consumer experience literature broadens in scope—specifically, from dyads to ecosystems and from provider-centric to consumer-centric perspective—traditional data collection methods are no longer adequate. In that context, the paper discusses three little-used data collection methods that can contribute to this broader view of consumer experience.
Design/methodology/approach: The article identifies methodological requirements for exploring the broadened view of consumer experience and reviews data collection methods currently in use.
Findings: The paper elaborates tailored guidelines for the study of consumer experience through first-hand, systemic and processual perspectives for three promising and currently underused data collection methods: phenomenological interviews, event-based approaches and diary methods.
Research limitations/implications: Although the list of identified methods is not exhaustive, the methods and guidelines discussed here can be used to advance empirical investigation of consumer experience as more broadly understood.
Practical implications: Practitioners can apply these methods to gain a more complete view of consumers’ experiences and so offer value propositions compatible with those consumers’ lifeworlds.
Originality/value: The paper principally contributes to the literature in two ways: by defining the methodological requirements for investigating consumer experience from consumer-centric, systemic and processual perspectives, and by specifying a set of data collection methods that meet these requirements, along with tailored guidelines for their use.